The development of mathematics teaching materials based higher order thinking skills in improving logical thinking skills - Anriani, Nurul; Pamungkas, Aan S. (Universitas Pendidikan Ganesha, 2018)
The purpose of this research is to produce a mathematics material based on high order thinking skills in improving the logical thinking skills of junior high school students. The material in this resource is â€˜SOLIDâ€ for junior high school students of class VIII. This research is research and development. The development model used includes potential problems, information gathering, product design, design validation, design improvements, product trials, and product revisions. The test of validity and practicality of the product is assessed by experts, teachers and students. The final product trial was conducted in several schools in Banten province. Effectiveness is tested using inferential statistical by looking at the significant difference of pretest and post-test value regarding students' logical thinking skills. The results showed that the product of development results including the category is very valid according to the experts, practically according to the assessment of teachers and students. The resulting product was also effective according to the mean difference test showing that there were significant differences before and after the teaching materials were given at a significance level of 5%.